Boosting Human Capital in the Philippines through Conditional Cash Transfers - Global Delivery Initiative (Global Delivery Initiative, Washington, DC, 2020)
Human capital is the Philippines’ most important resource. By the late 2000s, remittances from skilled and semi-skilled Filipinos working abroad were increasingly vital for many families, even as the country became one of the preferred destinations for foreign enterprises looking for educated workers in countries where their business processes could be outsourced. There were concerns, however, that the Philippines was beginning to lose its human capital edge because of critical gaps in access to social services and in the quality of those services. The Philippines responded to this by adopting an ambitious national social agenda aimed at putting it on a more robust development path. This agenda included lengthening the secondary education cycle and creating a social health insurance program for all citizens, a population management program, and a conditional cash transfer program (King 2020). This delivery note focuses on the conditional cash transfer program. Called the Pantawid Pamilyang Pilipino Program, which roughly translates into “building bridges for Filipino families” (Schelzig 2015), the initiative, first implemented in 2007, was designed to assist the poor by directly providing them with money. Unlike conventional social assistance programs, however, the beneficiaries received the grants only if they fulfilled certain conditions. Those conditions include enrolling their children in school and ensuring that they maintain attendance rates of at least 85 percent, taking their children on regular clinic visits for basic health services (such as immunization and growth monitoring), and regularly attending sessions where the beneficiaries learned about topics such as family planning, good citizenship, and financial literacy (Kandpal et al. 2016).